2020
DOI: 10.3389/fpubh.2020.00381
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance of a COVID-19 Vaccine in Southeast Asia: A Cross-Sectional Study in Indonesia

Abstract: Introduction: Several vaccine candidates are being clinically tested in response to the 2019 coronavirus disease (COVID-19) pandemic. This study was conducted to assess the acceptance of a 50 or 95% effective COVID-19 vaccine, when it becomes available in southeast Asia, among the general population in Indonesia. Methods: A cross-sectional online survey was conducted between March 25 and April 6, 2020. Participants were asked if they would accept a free vaccine which was 95 or 50% effective. Using a logistic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

83
616
20
23

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 589 publications
(742 citation statements)
references
References 44 publications
83
616
20
23
Order By: Relevance
“…An online survey of the French population (conducted 10 days after the nationwide lockdown was introduced in March) found that 74% would use a vaccine [8]. A similar acceptance rate was reported in other surveys (conducted around March-April) of residents in the United States (67%-69%) [9,10], Indonesia (67% to 95% depending on the effectiveness of the vaccine) [11] and 73% for parts of Europe (Denmark, France, Germany, Italy, Portugal, the Netherlands, and the UK) [12]. The difference in acceptance rate documented in this study may be due to a single or combination of factor(s) including: (1) the variation in the wording of the question; (2) high level of confidence and trust in the Australian government [6] or (3) due to concerns about increasing local transmission which were high at the time.…”
Section: Discussionsupporting
confidence: 66%
“…An online survey of the French population (conducted 10 days after the nationwide lockdown was introduced in March) found that 74% would use a vaccine [8]. A similar acceptance rate was reported in other surveys (conducted around March-April) of residents in the United States (67%-69%) [9,10], Indonesia (67% to 95% depending on the effectiveness of the vaccine) [11] and 73% for parts of Europe (Denmark, France, Germany, Italy, Portugal, the Netherlands, and the UK) [12]. The difference in acceptance rate documented in this study may be due to a single or combination of factor(s) including: (1) the variation in the wording of the question; (2) high level of confidence and trust in the Australian government [6] or (3) due to concerns about increasing local transmission which were high at the time.…”
Section: Discussionsupporting
confidence: 66%
“…A study in Indonesia also reported that for a 95% effective COVID-19 vaccine, 93.3% would take it. 25 Another study in Malaysia revealed that 94.3% of the respondents will take COVID-19 vaccine. 26 Finding from our study also revealed that geographical location and acceptance of the COVID-19 vaccine are significantly associated.…”
Section: Discussionmentioning
confidence: 99%
“…The response required for dependent variables was either "YES" or "NO" 1. Vaccine acceptance: the question asked was developed in line with Harapan et al (9) (11) however, it was modi ed to suit our study design. The question was "If the government of Uganda is to provide free COVID-19 vaccine, would you accept to be vaccinated?…”
mentioning
confidence: 99%
“…2. Vaccine trial acceptance: the questions asked here were developed according to Harapan et al (9) and it was modi ed to suit our study design. The questions were "Have you ever participated in any vaccine trial before?"…”
mentioning
confidence: 99%